Behavioral and steroidogenic pharmacology of phenyl ring substituted etomidate analogs in rats - Megan McGrath; Alissa Hofmann; Douglas E. Raines (BMC, 2019)
Abstract Background Cushing's syndrome is an endocrine disorder characterized by the overproduction of adrenocortical steroids. Steroidogenesis enzyme inhibitors are the mainstays of pharmacological treatment. Unfortunately, they produce significant side effects. Among the most potent inhibitors is the general anesthetic etomidate whose GABAA receptor-mediated sedative-hypnotic actions restrict use. In this study, we defined the sedative-hypnotic and steroidogenesis inhibiting actions of etomidate and four phenyl-ring substituted etomidate analogs (dimethoxy-etomidate, isopropoxy-etomidate, naphthalene-etomidate, and naphthalene (2)-etomidate) that possess negligible GABAA receptor modulatory activities. Methods In the first set of experiments, male Sprague-Dawley rats were assessed for loss of righting reflexes (LoRR) after receiving intravenous boluses of either etomidate (1 mg/kg) or an etomidate analog (40 mg/kg). In the second set of experiments, rats were assessed for LoRR and their abilities to produce adrenocortical and androgenic steroids after receiving 2-h infusions (0.5 mg kg− 1 min− 1) of either etomidate or an etomidate analog. Results All rats that received etomidate boluses or infusions had LoRR that persisted for minutes or hours, respectively. In contrast, no rat that received an etomidate analog had LoRR. Compared to rats in the vehicle control group, rats that received etomidate analog infusions had plasma corticosterone and aldosterone concentrations that were reduced by 80-84% and 68-94%, respectively. Rats that received etomidate infusions had plasma corticosterone and aldosterone concentrations that were also significantly reduced (by 92 and 96%, respectively). Rats that received etomidate or isopropoxy-etomidate had significant reductions (90 and 57%, respectively) in plasma testosterone concentrations whereas those that received naphthalene-etomidate had significant increases (1400%) in plasma dehydroepiandrosterone concentrations. Neither etomidate nor any etomidate analog significantly affected plasma androstenedione and dihydrotestosterone concentrations. Conclusions Our studies demonstrate that the four phenyl-ring substituted etomidate analogs form a novel class of compounds that are devoid of sedative-hypnotic activities and suppress plasma concentrations of adrenocortical steroids but vary in their effects on plasma concentrations of androgenic steroids.